Efficacy and safety of the pudendal nerve block as a component of multimodal analgesia for cervical brachytherapy - Matthew Charles Knox; Niluja Thiruthaneeswaran; George Zhong; Alison Brand; Unine Herbst; Emily Flower; Jennifer Chard; Alison Salkeld (Clinical and Translational Radiation Oncology, 2025)
Introduction: Whilst an essential component of curative management, cervical brachytherapy is associated with considerable pain and discomfort, with analgesic protocols varying between institutions. We present the first series on adjunctive pudendal nerve block (PNB) in addition to routine anaesthesia. Methods: Retrospective review of patients receiving brachytherapy for cervical malignancies across two time periods, correlating to the institutional introduction of PNB. Technically, bilateral PNB was performed using 1 % ropivacaine under general anaesthesia and intravenous patient-controlled analgesia (PCA) was used post-operatively. Median pain scores (11-point numeric rating scale), acceptability of pain (<20 % of recorded scores ≥ 4), opioid requirement and adverse events are reported. Intracavitary with or without interstitial brachytherapy was performed as per EMBRACE-2 protocol. Results: 78 patients receiving 149 brachytherapy episodes were included, of which 95 episodes (64%) utilised PNB. 48% of cases required interstitial needles in both cohorts, with no significant differences in demographics.Median pain scores were lower in the PNB cohort (1 vs. 2.5; p = 0.003). PNB was associated with less episodes of unacceptable pain, as defined above (33 % vs. 63 %; p < 0.001). This benefit was sustained on binomial logistic regression, including such factors as number of interstitial needles, baseline opioid use and applicator model choice.PNB use was also associated with reduced opioid requirement via PCA (p < 0.001) and there were no differences in the incidence of hypotension, respiratory depression or nausea between cohorts. Conclusions: PNB is an effective and safe adjunct to general anaesthesia and intravenous PCA for cervical brachytherapy, with improved pain and reduced opioid requirements. We advocate for routine use of PNB in addition to multimodal analgesic regimens.